A capacidade contributiva - Gregorio, Argos Magno de Paula (2007)
This essay aims at analyzing the main aspects concerning the Ability to Pay principle given the depth and the relevance of the matter however, it makes it with no intent to reach its depletion. The exposition o the theme begins under the Language Theory point of view, and allows the reader, after some very short considerations about the subject, to conclude that the Ability to Pay principle is about elocution, flawed with ambiguity and imprecision. After its origin and evolution throughout History, one aims at demonstrating the effort of the Doctrine in creating its notion in order to, after that, introduce some theories created by the main Schools that dedicated themselves to its study. Its analysis allowed the formulation of the concept of the Ability to Pay principle through different criteria, which each one of them highlighted the theoretic orientation of both Brazilian and foreign masters who have adopted it. Subsequently, one introduces the different conceptions of the Ability to Pay principle and, after a brief exposition of the Systems and its classifications, one examines the inclusion of the former in the Positivistic Law System through its rise to category of Principle. At the end of this essay, departing from a brief reasonable discourse about the Principles to subsequently identifying those that form the Constitutional Brazilian Tax Subsystem, one demonstrates the harmonization between these and the Ability to Pay principle in order to finally establish its effectiveness and achievement trough the usage of the principles of pondering and reasoning